P Penetapan Kadar Flavonoid Dan Aktivitas Antioksidan Ekstrak Etaanol Daun Bangkal (Nauclea subdita (Korth) Menggunakan Spektrofotometri Uv-Vis - Ulfah, Annisa; Nastiti, Kunti; Kurniawati, Darini; Hakim, Ali Rakhman (Jurnal Pelayanan Kefarmasian dan Sains, 2024)
Background: One of the typical Kalimantan plants that can be used as a source of medicine and can be used as an herbal ingredient is the Bangkal Plant. On the leaves there are various compounds such as alkaloids, steroids, tannins and flavonoids. Compounds that have a strong pharmacological effect and have a role as an antioxidant are flavonoid compounds.Objective: This study aims to determine the levels of flavonoids and antioxidant activity of ethanol extract of Bangkal Leaf (Nauclea subdita (Korth).Methods: This study uses an extraction method using 70% ethanol solvent and is soaked for 3 × 24 hours, the viscous extract produced is carried out a qualitative test with the identification of metabolite compounds and a quantitative test with the determination of flavonoid levels and antioxidant activity.Results: The results of the identification of metabolite compounds using color reagents obtained ethanol extract of Bangkal Leaf (Nauclea subdita (Korth) containing alkaloid compounds, steroids, tannins and flavonoids. The flavonoid level is 9.524 mgQE/g. The antioxidant activity of ethanol extract of Bangkal Leaf (Nauclea subdita (Korth) showed an IC50 value of 3.424 ppm.Conclusion: Based on the results of research that has been carried out, public knowledge relates to the rational use drugs for toothache. The need for information and education related to the use of drugs for tootchache rationally